STIMULATION OF ANTERIOR PITUITARY ADENYL CYCLASE ACTIVITY AND ADENOSINE 3′:5′-CYCLIC PHOSPHATE BY HYPOTHALAMIC EXTRACT AND PROSTAGLANDIN E(1) - Zor, Uriel (1969)
Hypothalamic extract, containing the releasing factors for anterior pituitary hormones, within minutes stimulated adenyl cyclase activity and adenosine 3′:5′-cyclic phosphate (cyAMP) concentrations in rat anterior pituitary in vitro. Cerebral cortical extract was ineffective and hypothalamic extract had no effect on these parameters in posterior pituitary or thyroid. Prostaglandin E(1) also increased adenyl cyclase activity and cyAMP levels in anterior pituitary tissue. Although NaF augmented adenyl cyclase activity, it did not elevate cyAMP. Epinephrine, norepinephrine, histamine, serotonin, dopamine, and vasopressin did not increase either adenyl cyclase or cyAMP. The increased adenyl cyclase and cyAMP produced by hypothalamic extract was associated with greater luteinizing hormone release from anterior pituitary in vitro.